2009
DOI: 10.1097/mog.0b013e3283279668
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic fibrosis

Abstract: Purpose of review This review will summarize the most significant work that contributed to the understanding of liver fibrosis progression and resolution, which in turn has yielded new areas of therapeutic targeting. Recent findings Liver fibrosis is the result of an imbalance between production and dissolution of extracellular matrix. Stellate cells, portal myofibroblasts, and bone marrow derived cells converge in a complex interaction with hepatocytes and immune cells to provoke scarring in response to liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
147
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(150 citation statements)
references
References 57 publications
1
147
0
2
Order By: Relevance
“…This correlates directly with the histologic features of human SOS where a significant proportion of patients develop centrilobular perisinusoidal and vein occlusive fibrosis (1,2,4,15,40). In the animal model deposition of collagen in the sinusoids also occurs, albeit as late event (18), when activated, HSC acquire a myofibroblastic phenotype and are essential actors in hepatic fibrosis (41) as underlined by the diffuse perisinusoidal aSM actin expression (1).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This correlates directly with the histologic features of human SOS where a significant proportion of patients develop centrilobular perisinusoidal and vein occlusive fibrosis (1,2,4,15,40). In the animal model deposition of collagen in the sinusoids also occurs, albeit as late event (18), when activated, HSC acquire a myofibroblastic phenotype and are essential actors in hepatic fibrosis (41) as underlined by the diffuse perisinusoidal aSM actin expression (1).…”
Section: Discussionmentioning
confidence: 91%
“…Our molecular observation could partially explain this clinical observation. VEGF blockade by bevacizumab could lead to downregulation of MMP expression by SEC (41,46), and thus attenuate sinusoidal lesions. VEGF-C mRNA was increased in SOS whereas VEGF-A remained at the same level as in controls.…”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro experiments of Oben et al 10 had shown that HSCs that are crucial for sinusoidal fibrosis producing most of the interstitial ECM 24 express a-and b-adrenoceptors. Additionally, HSCs are able to biosynthesize catecholamines because of their subset of metabolizing enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…There is overwhelming evidence that activated hepatic stellate cells (HSCs) are the major producers of the fibrotic neomatrix, although additional cellular sources, such as portal myofibroblasts, bone marrow-derived cells and epithelial-tomesenchymal transition (EMT), have been reported (Forbes and Parola, 2011;Jiao et al, 2009). Upon liver injury, quiescent HSCs undergo phenotypic transition into myofibroblast-like cells, which is invariably associated with loss of cytoplasmic vitamin A-containing lipid droplets, positive staining for α-smooth muscle actin (α-SMA), and greatly increased synthesis of the ECM proteins (Friedman, 2008).…”
Section: Introductionmentioning
confidence: 99%